The impact of resting heart rate measured on cardiovascular events in subject with hypertension. (25th November 2020) - Sobieraj, P; Lewandowski, J; Sinski, M
Abstract: Background: Available evidence does not indicate whether resting heart rate (RHR) is an independent risk factor or just marker of elevated risk. None of the studies assessed impact of RHR on cardiovascular events, when RHR was measured using automated blood pressure measurements (AOBPM). Purpose: To assess the relationship between RHR (measured using AOBPM) and cardiovascular events risk in subjects with hypertension. Methods: The data of SPRINT trial obtained via NHLBI were used to perform the analysis. SPRINT trial assessed intensive lowering of systolic BP to a target <120 mm Hg in comparison to standard goal (<140 mm Hg). RHR was measured using AOBPM device and calculated as an average of 3 measurements during the baseline visit of the study. Clinical composite endpoint (CE) of the study was defined as: myocardial infarction, acute coronary syndrome, decompensation of heart failure, stroke or cardiovascular death. The relationship between RHR and CE was assessed according to presence of cardiovascular disease (CVD) in past medical history. The statistical methods included t-test and chi-square test, Cox proportional risk models. The Cox models were adjusted for adjusted for age, sex, current smoking status and mean SBP during the trial. Restricted cubic splines were used to describe the relationship between RHR and hazard ratio. Results: Data of 1877 participants with CVD and 7484 participants without CVD were analyzed. Subjects with cardiovascular disease were older (69.7±9.5 vs 67.5 years ± 9.4, p<0.001), more often were men (72.8% vs 62.3%, p<0.001) and had prior chronic kidney disease (34.3% vs 26.8%, p<0.001) than subjects without CVD. CE was more than twice often when CVD was present (10.9% vs 4.8%, p<0.001). RHR was lower in subjects with CVD disease than in subjects without CVD (63.6±11 vs 66.9±11.6 bpm, p=0<00.1). Elevated RHR was associated with increased risk both in subjects with and without CVD (Figure 1). The multivariable Cox proportional hazard risk model revealed that RHR>80 bpm is an independent risk factor for CE in subjects without CVD (hazard ratio 1.37, 95% CI 1.01–1.85, p=0.043) while not in subjects with CVD (hazard ratio 0.99, 95% CI 0.57–1.71, p=0.98). Conclusion: Elevated RHR (>80 bpm) measured using AOBPM is an independent risk factor for cardiovascular events in subjects with hypertension and without CVD. Funding Acknowledgement: Type of funding source: None